PRAGMATIC ANALYSIS ON BEST SELLING NOVEL A WALK TO REMEMBER BY NICHOLAS SPARKS - Moondi Emsita (Universitas Gadjah Mada, 2013)
A Walk to Remember by Nicholas Sparks is one of The best-selling novels which is able to attract readers’ attention. Accordingly, a question of what elements of romance attract readers in choosing A Walk to Remember as their reading arase. Pragmatic approach was used to help find the romance formula based on the readers’ responses from internet sources. The result of the study showed that the readers of the novel were interested in the romance since it was not merely a love story, but it was also a story which presented moral values. In addition, this novel was able to attract readers since the romance story in the novel didn’t end happily. This novel was considered as more than a romance, it could be considered a drama.